THE INFLUENCE OF PARENTAL NEGLIGENCE ON THE EMOTIONAL STATE OF THE CHILD - O. I. Yadgarova; Abduvalieva Gavkhar (Web of Journals Publishing, 2023)
This article describes how the indifferent attitude of parents towards a child in the family negatively affects the mental state of the child. As a result of parents' neglect of the child's needs, due to lack of care for him, the child's emotional state is disturbed; such an attitude poses a threat to the health or mental development of the child. Some recommendations are also given for working with mental disorders in the child's psyche.
Keywords: education, child psychology, responsibility, attention, education, success, family relationships, mental health.